1999
DOI: 10.1017/s0140525x99001788
|View full text |Cite
|
Sign up to set email alerts
|

Verbal working memory and sentence comprehension

Abstract: This target article discusses the verbal working memory system used in sentence comprehension. We review the concept of working memory as a short-duration system in which small amounts of information are simultaneously stored and manipulated in the service of accomplishing a task. We summarize the argument that syntactic processing in sentence comprehension requires such a storage and computational system. We then ask whether the working memory system used in syntactic processing is the same as that use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

45
673
8
17

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 763 publications
(752 citation statements)
references
References 212 publications
45
673
8
17
Order By: Relevance
“…These results are not fully consistent with either of the two dominate theories of working memory and language processing, the CC model of Just and Carpenter (1992) (also the 3CAPS model of Just & Varma, 2002) or the SLIR model of Waters and Caplan (1996a;Caplan & Waters, 1999). The CC model argues that the capacity of working memory constraints language processing as well as other cognitive abilities.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…These results are not fully consistent with either of the two dominate theories of working memory and language processing, the CC model of Just and Carpenter (1992) (also the 3CAPS model of Just & Varma, 2002) or the SLIR model of Waters and Caplan (1996a;Caplan & Waters, 1999). The CC model argues that the capacity of working memory constraints language processing as well as other cognitive abilities.…”
Section: Discussionmentioning
confidence: 70%
“…High span readers allocated additional fixation time to the Subject NP marked by the ONLY operator in order to assess its discourse function; low span readers did not appear to be sensitive to the discourse function of ONLY. First pass fixations by all readers revealed a garden-path effect for the ambiguous THE sentences; however, high span readers, unlike low span readers, were now able to avoid the garden-path effect for the ONLY sentences because they had allocated extra first pass fixation time to Subject NPs marked by the ONLY operator,.These results are not fully consistent with either of the two dominate theories of working memory and language processing, the CC model of Just and Carpenter (1992) (also the 3CAPS model of Just & Varma, 2002) or the SLIR model of Waters and Caplan (1996a;Caplan & Waters, 1999). The CC model argues that the capacity of working memory constraints language processing as well as other cognitive abilities.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…A morphological left-over-right asymmetry was found for BA44, but not for BA45 (Amunts et al, 1999). Broca's area was shown to be involved in syntactic processes in a number of neuropsychological studies, in particular in that patients with lesions including Broca's area clearly suffering from syntactic deficits (Grodzinski, 2000;Caplan and Waters, 1999). In addition, some recent brain imaging studies have demonstrated increased hemodynamic activity in Broca's area during the processing of syntactic aspects during language comprehension (Dapretto and Bookheimer, 1999;Embick et al, 2000;Friederici et al, 2000a;Just et al, 1996;Moro et al, 2001;Tettamanti et al, 2002).…”
Section: Discussionmentioning
confidence: 99%